Caracterização molecular de isolados de Mycobacterium bovis de rebanhos de diferentes regiões do Brasil - Ramos, Daniela Fernandes (2012)
Bovine tuberculosis (BTB) caused by Mycobacterium bovis is an infectious disease of zoonotic which mainly affects cattle and buffaloes, and cause economic losses in the production of meat and milk in many countries. In Brazil, the official rates are at 1.3% of the national herd infected, corresponding to approximately 2.5 million animals. To contribute to the control of BTB, many molecular techniques have been developed in order to differentiate isolates and establish epidemiological correlations between them. Among these techniques, the most used are the Restriction Fragment Lenght Polymorphism (RFLP), Polymorphic Guanine-cytosine-Rich Sequence [1], Spoligotyping [2], Mycobacterial Interspersed Repetitive Units - Variable Number of Tandem Repeat (MIRU-VNTR) and Exact Tandem Repeat [3]. The spoligotyping and MIRU-VNTR are today considered standard methods of molecular techniques for typing of M. bovis. Both are based on PCR techniques that evaluate polymorphism in the number of repeat sequences present in the genome. Taking into account that the molecular characterization enables to increase our knowledge on the epidemiology of M. bovis and in tuberculosis control, this study aimed at the molecular characterization of isolates of M. bovis in the north and south of the Brazil, by isolating agent, identification of M. bovis by amplification of the region RD7 Multiplex PCR and genotyping using the techniques of spoligotyping, MIRU-VNTR and ETR. Nine-nine lymph nodes were collected from beef cattle in the north of the region and 162 dairy cattle in southern Brazil, and only 10 samples were positive for M. bovis in the north and 85 in the south region. Through analysis of molecular combination of spoligotyping and VNTR was possible to identify different genotypic patterns in the regions studied demonstrating the genetic diversity of M. bovis in our country.